Effects of Bio-Pesticides on Biology of Chrysoperla carnea F. (Neuroptera: Chrysopidae) - S. Shahzad Ali,; M.Y. Khaskheli,; S. Sohail Ahmed,; Huma Rizwana,; Aslam Bukero,; Gulzar Thebo,; Shahzad Ali Nahyo,; Irshad Ali Rattar ,; Sarfraz Ahmad, (Journal of Basic & Applied Sciences, 2015)
The experiment was conducted on effects of bio-pesticides on biology of Chrysoperla carnea F. under laboratory conditions. The neem and datura leaf extracts were used as bio-pesticides and their effect was compared with confidor at 26±2°C, 65±5% R. H and photoperiod (16L: 8D) in the | department of Entomology, Sindh Agriculture University, Tandojam, Pakistan during 2014. The results shows that the incubation periods of eggs of C. carnea feeding on Aphis gossypii treated with neem, datura and confidor was 2.2, 2.5 and 3.6 days respectively. The result indicated that the total larval developmental period was 17.03, 13.3 and 15.09, respectively. The pupal period of C. carnea was 8.82 on neem, 10.9 on datura and 12.33 days on confidor. The result further revealed that the pre oviposition period of C. carnea was 6.35 on neem, 5.5 on datura and 3.6 on confidor. The oviposition period was 34.42 on neem, 30.6 on datura and 26.4 on confidor. The post oviposition period was significantly different was 8.5 days on neem 6.9 on datura and 4.7 on confidor. The maximum fecundity per female of C. carnea was 448.38 days on neem, 435.67 on datura and 413.67 on confidor. Similarly, maximum egg hatching percentage of C.carnea was recorded on neem followed by datura and confidor. However, the maximum egg mortality (37.65%) was recorded on confidor. However, minimum mortality of 1st, 2nd and 3rd instar larvae was recorded due to neem leaf extracts followed by datura and confidor. The pupal mortality was seen more on neem followed by datura and confidor. The highest adult mortality was obtained on neem followed by datura and confidor insecticide.